Against Emotional Dogmatism. Issue 1 (October 2016) - Brogaard, Berit; Chudnoff, Elijah
Abstract : It may seem that when you have an emotional response to a perceived object or event that makes it seem to you that the perceived source of the emotion possesses some evaluative property, then you thereby have prima facie, immediate justification for believing that the object or event possesses the evaluative property. Call this view 'dogmatism about emotional justification'. We defend a view of the structure of emotional awareness according to which the objects of emotional awareness are derived from other experiences such as bodily sensation, inner awareness, sensory perception, memory, and imagination. On this basis, we argue that dogmatism about emotional justification is an untenable position, regardless of whether the special feature of an immediate justifier that makes it an immediate justifier is its presentational phenomenology or its evidence insensitivity.